Application of information technologies of automation designing for research of designs on nonlinear the deformed basis - Слободян, Я.О.; Білеуш, А.І.; Євтодій, О.О.; Шаравара, Н.П. (Proceedings of National Aviation University (archive), 2004)
The results of numerical researches of designs on nonlinear the deformed basis with application of modern information technologies of automation designing are given on the basis of a program complex LIRA also estimation of an error of the decision of a nonlinear task by a step-by-step method.